The practice of fasting in christian spirituality - Hintz, Bruno Bernardi; Butzke, Paulo Afonso (Vox Scripturae - Revista Teológica Internacional, 2017)
Fasting is a spiritual exercise that appears in the Bible and has been practiced throughout the history of the Church, but it is little discussed in today’s Christian communities, and around it many doubts circulate. Although fasting is present in several religions, this research focused on its significance for the Christian faith, with the intention of offering answers to questions on this subject from a biblical perspective. To this end, at first it was sought to apprehend the vision that the Old Testament and the New Testament have on the fast. Then an analysis of fasting was made throughout the history of the Church, how it happened and for what purpose it was employed from the old church to the Reformation, through the monks and nuns of the desert and the monasteries. Finally, we wondered about the place of fasting in Christian spirituality, and how fasting concerns Christians in today’s world.
Keywords: Fasting; Spirituality; Ascese; Spiritual Exercises; Practical theology